Neurologic outcomes in pediatric cardiac arrest survivors enrolled in the THAPCA trials. (10th July 2018) - Ichord, Rebecca; Silverstein, Faye S.; Slomine, Beth S.; Telford, Russell; Christensen, James; Holubkov, Richard; Dean, J. Michael; Moler, Frank W.
Abstract : Objective: To implement a standardized approach to characterize neurologic outcomes among 12-month survivors in the Therapeutic Hypothermia after Pediatric Cardiac Arrest (THAPCA) trials. Methods: Two multicenter trials enrolled children age 48 hours to 18 years who remained comatose after cardiac arrest (CA) occurring out-of-hospital (THAPCA-OH, NCT00878644) or in-hospital (THAPCA-IH, NCT00880087); patients were randomized to therapeutic hypothermia or therapeutic normothermia. The primary outcome, survival with favorable 12-month neurobehavioral outcome (Vineland Adaptive Behavior Scales [VABS-II]), did not differ between treatment groups in either trial. Neurologists examined 181 12-month survivors, described findings using the novel semi-quantitative Pediatric Resuscitation after Cardiac Arrest (PRCA) form, and rated findings in 6 domains; scores ranged from 0 (no deficits) to 21 (maximal deficits). PRCA scores were compared with 12-month VABS-II scores and cognitive scores. Results: Neurologic outcome PRCA scores were classified as no/minimal impairment, PRCA 0–3, 81/179 (45%); mild impairment, PRCA 4–7, 24/179 (13%); moderate impairment, PRCA 8–11, 15/179 (8%); severe impairment, PRCA 12–16, 20/179 (11%); profound impairment, PRCA 17–21, 39/179 (21%) (2/181 incomplete). VABS-II scores correlated strongly with PRCA category ( r = −0.88, p < 0.0001, Pearson correlation coefficient) and cognitive scores ( r = −0.72, p < 0.0001). Factors associated with poor outcomes included out-of-hospital CA, seizure recognition in the early postarrest period, and poor neurologic status at hospital discharge. Conclusion: The PRCA provides a robust method for depicting neurologic outcomes after acute encephalopathy caused by CA in children. It provides a global semiquantitative rating of neurologic impairment and domain-specific impairment. The strong correlation with well-established neurobehavioral outcome measures supports its validity over a broad age range and wide spectrum of outcomes.